Menutup Celah Korupsi Pemerintahan Daerah - Muhadam Labolo (Lembaga Riset dan Pengkajian Strategi Pemerintahan (LRPSP), Institut Pemerintahan Dalam Negeri (IPDN), 2017)
The phenomenon of corruption now enters a nearly immeasurable area. Horizontally corruption spreads in almost all branches of power, both legislative, executive and judiciary. On a vertical line of corruption perched in every government hirakhi, from the center of power to the lowest level. In the case of Indonesia, since reformation has peaked (1998), corruption is like getting a decent place to breed. In the new order period until its downfall, executive dominance made corrupt behavior as stored neatly in documents only known by the regime in power. In curative action, there is no effective way to control corruption loopholes in the local government environment, except to impose strict sanctions, both administrative and legal for companies / entrepreneurs, government officials and communities who commit fraud in the use of APBD, procurement of goods and services, Business licensing and election services. Those who are administratively and legally proven should be immediately reduced, eliminated, substituted, disqualified and executed to produce deterrent effects for the community. Such action can be carried out directly for matters concerning the use of facilities and the budget of the agencies for the interests of the election, the implementation of the standard budget of the regional head election, close the space for the incumbent who want to re-nominate head of region if proven to conduct corruption.Keywords: Corruption, Local Government, Reform, Regional Autonomy